2022
DOI: 10.3389/fimmu.2022.784443
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophils Present Mild Activation by Zika Virus But Reduce the Infection of Susceptible Cells

Abstract: The emergence of the Zika virus (ZIKV) has highlighted the need for a deeper understanding of virus-host interactions in order to pave the way for the development of antiviral therapies. The present work aimed to address the response of neutrophils during ZIKV infection. Neutrophils are important effector cells in innate immunity implicated in the host’s response to neurotropic arboviruses. Our results indicate that human neutrophils were not permissive to Asian or African ZIKV strain replication. In fact, aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…We find that ZIKV is not captured by NETs, which implies that there is a viral escape strategy targeting NET‐mediated mechanisms such as entrapment and killing. Similar to our results, it has been shown that NETs did not trap ZIKV 56 . Thus, ZIKV seems to have developed strategies to inhibit the NET formation and its virucidal effect by modulating ROS production and possibly other pathways necessary for NET formation, not yet identified.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We find that ZIKV is not captured by NETs, which implies that there is a viral escape strategy targeting NET‐mediated mechanisms such as entrapment and killing. Similar to our results, it has been shown that NETs did not trap ZIKV 56 . Thus, ZIKV seems to have developed strategies to inhibit the NET formation and its virucidal effect by modulating ROS production and possibly other pathways necessary for NET formation, not yet identified.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our results, it has been shown that NETs did not trap ZIKV. 56 Thus, ZIKV seems to have developed strategies to inhibit the NET formation and its virucidal effect by modulating ROS production and possibly other pathways necessary for NET formation, not yet identified.…”
Section: Discussionmentioning
confidence: 99%